MORAL PHILOSOPHY OF T. ADORNO: FROM CRITICAL THEORY TO MODERN PRACTICAL PHILOSOPHY - Leonteva , Sofia (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2021)
The task of philosophy according to Adorno is comprehension of universality and normativity. In spite of conceptual thinking debunked in negative philosophy, Adorno remains devoted to modernity project. His original philosophical thinking adherent to modernity presents an interesting constellation of ethical ideas, concepts of moral philosophy, around which a certain model of practical rationality can be constructed. The purpose of this article is the construction of practical philosophy of Adorno. Ideas of his essays on morality are analyzed in the perspective of normativity foundations of critical theory from the first generation of Frankfurt School to discourse ethics and contemporary critical philosophy. The author outlines the divergence between Adorno’s philosophy and discourse ethics in the matter of justification of normativity implemented in formal procedure of communication. Following Kant’s foundation of morality Adorno provides a richer account of controversies which are subject of contemporary critical theory. Adorno’s thinking elucidates the ambiguity of universality in the concept of “inner dialectic of morality”. He rejects the abstract morality and reveals its repressive features. Instead he puts the concept of humanity in the center of his examination. Morality defined as law and equality, justified by procedure of reasoning appears abstract. In contrast Adorno draws attention to moral impulse which invokes moral deed. Dialectic of morality unfolds in the opposition of impulse, solidarity, affection towards others on the one hand, and autonomy and equality underlying external side of moral law – on the other. Thus individuality modus is the source of morality while abstract formalism of universalism is avoided on the basis of reflection of morality with ethical virtues of critical thinking, humility and affection. Moral principles stand for theoretical aspect and justification of normativity, impulsion concerns application of morality. Thus the problem of contradiction of universalism and contextualism is elucidated through reconciliation of right as moral law and ethical good.